The functioning of the system of cyclic nucleotides in the conditions of influence of extracellular physiologically active substances - Puhteeva, Irina V.; Gerasimovich, Natalya V.; Rybachenok, Dorothea S. (Journal of the Belarusian State University. Ecology, 2018)
The purpose of the work is to analyze possible changes of concentration of cyclic nucleotides in cells of the immune system of rats at influence of purine nucleotides. The objects of the research were thymus cells (thymocytes) and lymphocytes of peripheral blood of rats. The maintenance of intracellular cAMF and cGMP was defined by a radio immune method by means of reference sets (IBOH NAN RB). It is showed that purine nucleotides in different degrees affect the system of cyclic nucleotides in thymocytes and lymphocytes of peripheral blood. So, exogenous ATP authentically increased the maintenance of cAMF and cGMP in thymocytes, and the system of cyclic nucleotides in lymphocytes of peripheral blood showed pronounced changes at action of an adenosine. Results of this work can have important practical value from the point of view of deepening of ideas of realization of molecular mechanisms of influence of various biologically active agents through system of cyclic nucleotides as one of the main intracellular intermediaries.